2003
DOI: 10.1016/s0006-291x(03)01392-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators expressed in human islets of Langerhans: implications for islet transplantation

Abstract: Expression of immune modulating mediators in human Islets of Langerhans could have important implications for development of autoimmunity in type 1 diabetes and influence the outcome of clinical islet transplantation. Islets obtained from five donors were analyzed at various times after isolation using cDNA array technology. The Atlas Human Cytokine/Receptor and Hematology/ Immunology nylon membranes representing 268 genes and 406, respectively, were used and the relative expression of each gene analyzed. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 41 publications
6
122
1
Order By: Relevance
“…Human pancreatic islets Human pancreatic islets were isolated from three donors (one female and two males) and purified at the Uppsala University Hospital (coordinator, Prof. Olle Korsgren) as previously described [15], with the consent of the ethics committee of Uppsala University. The donor age varied between 45 and 74 years and cold ischaemia time between 6 h and 8 h 54 min.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human pancreatic islets Human pancreatic islets were isolated from three donors (one female and two males) and purified at the Uppsala University Hospital (coordinator, Prof. Olle Korsgren) as previously described [15], with the consent of the ethics committee of Uppsala University. The donor age varied between 45 and 74 years and cold ischaemia time between 6 h and 8 h 54 min.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…IFIT1: 2 and 4 interferon-induced protein with tetratricopeptide repeats 1, 2 and 4 . IFITM1: interferon-induced transmembrane protein 1 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) . IFNB1: interferon β1, fibroblast .…”
mentioning
confidence: 99%
“…Thus, VEGF may be expected to ameliorate damage to islets in the immediate post-transplant period. Array technology has shown that isolated human islets express VEGF [25], and it has been reported that VEGF protein is co-expressed with insulin [26], as in the rat. The production of VEGF receptors by human islets has not been characterised in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, porcine islets that have been cultured for at least 24 h are significantly better at reversing hyperglycaemia when transplanted into diabetic nude mice compared with freshly isolated islets [19]. In addition, there is a much higher relative expression of inflammatory genes during the immediate post-isolation period when compared with islets cultured for 1 week [20]. Culturing islets also provides an opportunity for therapies aimed at improving islet survival, inducing islet expansion, and reducing islet immunogenicity.…”
mentioning
confidence: 99%